Cooperative detection of primary user emulation attacks based on channel–tap power in mobile cognitive radio networks. (27th May 2014) - Chin, Wen–Long; Le, Trong Nghia; Tseng, Chun–Lin; Kao, Wei–Che; Tsai, Chun–Shen; Kao, Chun–Wei
This work proposes a new method for identifying a primary user emulation attack (PUEA) at low signal–to–noise ratios (SNRs) in mobile cognitive radio (CR) networks. Channel–tap power is utilised as a radio–frequency (RF) fingerprint to directly detect users via physical (PHY) layer. To improve the detection performance in fading channels, the cooperative detection schemes using the fixed sample size test (FSST) and the sequential probability ratio test (SPRT) are devised. From simulation results, for a mobile CR speed of 70 km/h, SNR = –5 dB and false alarm probability of 0.03, the FSST using 10 cooperative nodes can achieve the detection probability of 0.99, which is increased by 1.94 times that of the single Neyman–Pearson detector. When the SPRT is compared to the FSST, the SPRT only needs less than half of the detection time of the FSST to provide the same detection performance for all SNRs considered.